TWO METHODS OF SOLVING THE SYSTEM OF DIFFERENCE AND INTERVAL CONSTRAINTS - I. V. Rubanov; M. S. Barketau; M. Y. Kovalyov (Informatika)
We develop two methods of solving DBM system. One method is based on Fourier – Motskinelimination scheme, it has complexity O(n3) for finding initial solve and complexity O(n3) for finding solve by changing one of variable value for some cases. The other method is based on the network of constraints approach, it has complexity O(n3) for finding initial solve and  O(n) or approximately for finding solve by changing one of variable value if it is limited by special bounds.